1985
DOI: 10.1212/wnl.35.6.921
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide‐induced parkinsonism

Abstract: An 18-year-old man ingested 975 to 1,300 mg of potassium cyanide in a suicide attempt. He was treated and survived the poisoning episode, but then had severe parkinsonian syndrome, characterized primarily by akinesia and rigidity. He died 19 months after the drug overdose. At autopsy, major destructive changes were found in the globus pallidus and putamen, whereas the melanin-containing zone of substantia nigra was intact. This is the first clinicopathologic report of parkinsonism as a result of cyanide poison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…This is the same abnormality reported in naturally occurring sporadic PD [85]. Further support for possible causation of PD by defects in electron transport chain is provided by the observation that a parkinsonian syndrome is sometimes a residual of cyanide poisoning, a known inhibitor of several functions of the electron transport chain [88].…”
Section: Abnormalities Of the Electron Transport Chain In Idiopathic Pdsupporting
confidence: 76%
“…This is the same abnormality reported in naturally occurring sporadic PD [85]. Further support for possible causation of PD by defects in electron transport chain is provided by the observation that a parkinsonian syndrome is sometimes a residual of cyanide poisoning, a known inhibitor of several functions of the electron transport chain [88].…”
Section: Abnormalities Of the Electron Transport Chain In Idiopathic Pdsupporting
confidence: 76%
“…Cyanide toxicity can manifest as a Parkinson-like syndrome as a result of dopaminergic cell death in basal ganglia (Uitti et al, 1985). In the present study, cell death was observed in midbrains of mice repeatedly treated with cyanide as described by Mills et al (1999) with use of the same duration and dose of KCN treatment.…”
Section: Bnip3 Up-regulation In Mousesupporting
confidence: 62%
“…Cyanide is a classic mitochondrial toxicant associated with a secondary Parkinsonism that occurs after severe, acute intoxication (Uitti et al, 1985;Sarikaya et al, 2006). In sublethal toxicity, a postintoxication sequalae can manifest as akinesia and rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…Some sequelae of cyanide toxicity in humans have been associated with damage to the basal ganglia, including Parkinsonian symptoms (Finelli, 1981;Uitti et al, 1985;Carella et al, 1988;Rosemberg et al, 1989;Feldman and Feldman, 1990;Messing, 1991), phobic anxiety (Nicholson and Vincenti, 1994) and psychosis (El Ghawabi et al, 1975;Kales et al, 1997). Furthermore, cyanide intoxication has been linked to personality change in a man (Uitti et al, 1985).…”
Section: Discussionmentioning
confidence: 99%